Desain Kemasan, Kualitas Produk, dan Harga dalam Pengaruhnya Terhadap Minat Beli Konsumen By. Uwibama - Mutiarini Mubyl; Mariah Mariah; A. Lutfiah Saskia (Jurnal Mirai Management, 2021)
This study aims to examine packaging design, product quality, and price in their influence on consumer buying interest. The research design used was quantitative with the number of respondents as many as 100 By. Uwibama’s consumers. This study was analyzed using SPSS 20.0 to test the validity and reliability of items, as well as normality, multicollinearity, heteroscedasticity, autocorrelation, and regression tests to determine the effect of variables partially or simultaneously. The results show that packaging design and price have a positive and partially significant effect, while product quality has no positive and partially significant effect. The results of the F test show that the packaging design, product quality, and price have a simultaneous positive and significant effect on consumers' buying interest in By. Uwibama. The most dominant variable in influencing the buying interest of By.Uwibama’s products is a price variable. Keywords : packaging design, product quality, price, buying interest